Penanggulangan Stunting Melalui Modal Sosial di Desa Besmarak Kecamatan Nekamese Kabupaten Kupang - N, Nursalam; Neolaka, Melkisedek N.B.C.; Djani, William; Toda, Hendrik (Idea Pengabdian Masyarakat, 2021)
Stunting is one of the public problems that need attention and handling. The incidence of stunting if left unchecked can have implications for the quality of human resources, namely in addition to risking physical growth barriers and children’s vulnerability to disease, it also causes cognitive development barriers that will affect children’s intelligence and productivity levels in the future. The community service (PPM) which is carried out in the form of counseling in Besmarak village, Nekamese sub-district, Kupang regency is expected to provide knowledge to the community that solving the stunting problem is not only through health and nutrition improvement assistance provided by the government, but also through community social capital, namely through social networks and community trust norms. There is a strong relationship between social capital and solving various public problems, so that people with higher social capital also have higher awareness, they are able to take collective action in preventing stunting.